Enhanced degradation of organic water pollutants using lead-free ferroelectric photocatalysts - Vaishali Gupta; Satyendra Singh (Chemistry of Inorganic Materials, 2024)
Advanced oxidation processes have attracted considerable attention for wastewater treatment, air purification, CO2 reduction and many more pollution control applications. Environmentally friendly (K0.5Na0.5)NbO3 (abbreviated as 'KNN') is emerging as a lead-free photocatalyst due to its good piezoelectric response and high Curie temperature. In this work, KNN photocatalysts were synthesized by two methods i.e. solid-state and sol-gel routes and abbreviated as KNN-SS and KNN-SG, respectively. X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) confirmed the orthorhombic structure for both the samples. Morphological studies were done using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Average particle size was estimated using ImageJ software which is to be around 1.38 ​μm and 278 ​nm for KNN-SS and KNN-SG samples respectively. Zeta potential measurements estimated the average surface charge on the particles i.e. 67.099 ​mV for KNN-SS and 69.115 ​mV for KNN-SG samples. Tauc’ plot was employed to find the optical bandgap, which was estimated around 3 ​eV for both the samples. Photoluminescence (PL) spectroscopy confirmed that KNN-SG sample has a lower recombination rate than KNN-SS sample as it exhibited lower emission intensity. Better photocatalytic result of 92.8 ​% degradation of methylene blue dye in just 80 ​min has been observed for KNN-SG sample, indicating smaller particle size causes delayed recombination, which enhances higher photodegradation of the material. Lead-free ferroelectric KNN samples with smaller particle sizes can be a promising candidate for these effluents.